Perlindungan Hukum dan Pencegahan Kejahatan Siber di Era Digital dalam Sistem Hukum di Indonesia - Firdaus, Rahma Agri (UIN Sunan Kalijaga Yogyakarta, 2024)
This research discusses aspects of legal protection and prevention of cybercrime in the digital era in the Indonesian legal system. The purpose of the research is to evaluate the effectiveness of criminal provisions in the Electronic Information and Transaction Law (ITE Law) and the role of the Personal Data Protection Law (PDP Law) as a preventive instrument. The research method used is a normative research model with a statutory approach to examine the text of the law and a philosophical approach to outline the urgency of legal protection related to cybercrime, as well as a conceptual approach to assess the suitability of norms against the legal objectives of justice, legal certainty, and expediency in the context of cyber resilience. The data analysis technique is carried out using a descriptive-qualitative model. The results show that the development of the digital world through technology and information has had an impact on the development of data security issues and the orderly use of internet technology. In Indonesia, the ITE Law has established various cyber offences with criminal sanctions, there are still overlapping norms, cross-border jurisdictional constraints, and still faced with limited digital forensic capacity of law enforcement officials. Meanwhile, the PDP Law provides a foundation for institutions and risk mitigation mechanisms through data protection, but has not been systemically integrated with criminal instruments. Thus, the main challenge of legal protection against cyber crime in the digital era is the synchronisation and optimisation of regulations and supporting tools in order to achieve cyber resilience and security. Abstrak Penelitian ini membahas aspek perlindungan hukum dan pencegahan kejahatan siber di era digital dalam sistem hukum di Indonesia. Tujuan penelitian adalah mengevaluasi efektivitas ketentuan pidana dalam Undang-Undang Informasi dan Transaksi Elektronik (UU ITE) serta peran Undang-Undang Perlindungan Data Pribadi (UU PDP) sebagai instrumen preventif. Metode penelitian yang digunakan adalah model penelitian normatif dengan pendekatan perundang-undangan (statute approach) untuk menelaah teks undang-undang dan pendekatan filosofis (philosophical approach) untuk menguraikan urgensi perlindungan hukum terkait cybercrime, serta pendekatan konseptual untuk menilai kesesuaian norma terhadap tujuan hukum keadilan, kepastian hukum, dan kemanfaatan dalam konteks ketahanan siber. Teknik analisis data dilakukan menggunakan model deskriptif-kualitatif. Hasil penelitian menunjukkan bahwa perkembangan dunia digital melalui teknologi dan informasi telah berdampak pada berkembangnya masalah keamanan data dan tata tertib penggunaan teknologi internet. Di Indonesia telah ada UU ITE telah menetapkan berbagai delik maya dengan sanksi pidana, masih terdapat tumpang tindih norma, kendala yurisdiksi lintas negara, dan masih dihadapkan keterbatasan kapasitas forensik digital aparat penegak hukum. Sementara itu, UU PDP memberikan landasan tentang kelembagaan dan mekanisme mitigasi risiko melalui perlindungan data, namun belum terintegrasi secara sistemik dengan instrumen pidana. Degan demikian tantangan utama perlindungan hukum terhadap kejahatan cyber di era digital adalah sinkronisasi serta optimalisasi regulasi dan perangkat pendukung yang mumpuni dalam rangka mencapai ketahanan dan keamanan cyber